Atherosclerosis and Microvascular Complications: Results From the Canadian Study of Longevity in Type 1 Diabetes - Lovshin, Julie A. (Diabetes Care, 2018)
OBJECTIVE: Type 1 diabetes carries a significant risk for cardiovascular mortality, but it is unclear how atherosclerosis associates with microvascular complications. We aimed to determine the relationships between atherosclerotic burden and neuropathy, retinopathy, and diabetic kidney disease (DKD) in adults with a ≥50-year history of type 1 diabetes. RESEARCH DESIGN AND METHODS: Adults with type 1 diabetes (n = 69) underwent coronary artery calcification (CAC) volume scoring by wide-volume computerized tomography. Microvascular complications were graded as follows: neuropathy by clinical assessment, electrophysiology, vibration and cooling detection thresholds, heart rate variability, and corneal confocal microscopy; retinopathy by ultra–wide-field retinal imaging; and DKD by renal hemodynamic function measured by inulin and para-aminohippurate clearance at baseline and after intravenous infusion of angiotensin II. The cohort was dichotomized to high (≥300 Agatston units [AU]) or low (<300 AU) CAC and was stratified by diabetes status. A comparator group without diabetes (n = 73) matched for age and sex also underwent all study procedures except for retinal imaging. RESULTS: CAC scores were higher in participants with type 1 diabetes (median Agatston score 1,000 [interquartile range = 222, 2,373] AU vs. 1 [0.75] AU in comparators, P < 0.001). In participants with type 1 diabetes, high CAC scores associated with markers of neuropathy and retinopathy, but not with DKD, or renal hemodynamic function at baseline or in response to angiotensin II. CONCLUSIONS: The presence of high CAC in adults with longstanding type 1 diabetes was associated with large nerve fiber neuropathy and retinopathy but not with renal hemodynamic function, suggesting that neuropathy, retinopathy, and macrovascular calcification share common risk factors.